Crossing boundaries: A pilot study of maternal attitudes about child maltreatment in nine countries - Mesman, Judi; Branger, Marjolein; Woudstra, Mi-lan; Emmen, Rosanneke; Asanjarani, Faramarz; Carcamo, Rodrigo; Hsiao, Celia; Mels, Cindy; Selcuk, Bilge; Soares, Isabel; van Ginkel, Joost; Wang, Lamei; et al. (My University, 2020)
Background: Definitions of child maltreatment vary widely between studies, and even more so between different cultural contexts. Objective: In this pilot study, we examine between-country variations in maternal notions about what constitutes child maltreatment. Participants and setting: The sample consisted of 466 mothers recruited in Chile, China, Greece, Iran, the Netherlands, Portugal, South Africa, Turkey, and Uruguay. Methods: All mothers completed a new Q-sort measure, ranking 90 parenting behaviors linked to subtypes of maltreatment (emotional neglect, emotional abuse, physical neglect, and physical abuse) from least to most detrimental to child development. Results: Between-country agreement regarding the harmfulness of the parenting behaviors was high (r=.45), but there were different patterns of reported harmfulness of subtypes of maltreatment (although driven mostly by deviating patterns in the South African sample). Further, there were significant country effects on the number and type of behaviors labeled as maltreatment (pre=.15), and the number of items labeled as requiring intervention (pre=.19). Conclusions: Variations in conceptions of maltreatment need to be studied in larger more representative samples and taken into account in the assessment and treatment of child maltreatment across cultures.
Keywords: child maltreatment; culture; attitudes; mothers